PENGARUH IDEALISME, RELATIVISME DAN PERSONAL VALUE PADA PERSEPSI MAHASISWA AKUNTANSI GEN Z ATAS PERILAKU TIDAK ETIS AKUNTAN - Jasmine, Angeline; Suwiryo, Darmo H; Tanjung, Hendra (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the influence of idealism, relativism and Personal Value on accounting students' perceptions of unethical behavior of accountants. The sample consisted of 120 accounting students of Muhammadiyah University of Sukabumi selected by purposive sampling method. The research method is quantitative with primary data sources, through questionnaires. The data analysis method uses multiple linear regression analysis with IBM SPSS 29 software. The results of the study show that idealism has a negative effect on the perception of gen z accounting students on unethical behavior of accountants. The higher the level of students' idealism, the higher their rejection of unethical behavior of accountants. Conversely, relativism has a positive effect on the perception of gen z accounting students on unethical behavior of accountants. The higher the level of students' relativism, the higher their tolerance for unethical behavior of accountants. Openness to Change, Conservation and Self-Transcendence have no effect on the perception of gen z accounting students on unethical behavior of accountants. However, Self-Enhancement has a negative effect on the perception of gen z accounting students on unethical behavior of accountants